Regional anaesthesia for district hospitals and clinics - Michele Torlutter (South African Family Practice)
Pain is a common reason that patients seek care in the emergency department (ED). Regional anaesthesia in the form of nerve blocks provides an excellent alternative to traditional forms of analgesia, and may be superior in managing musculoskeletal pain compared to opioids. Adequate pain management improves patient satisfaction, facilitates examination and minor procedures, and allows for earlier and safe discharge. In low resource settings this modality is underutilised due to lack of trained providers and/or support from specialised services, shortages of equipment, and lack of context-sensitive guidelines. Advances in ultrasound guided regional anaesthesia has the potential to improve access to safe and reliable anaesthesia. It is often not accessible or an active part of training even for emergency physicians. There are, however, a number of nerve blocks that are easy to learn, don’t require specialised equipment, and can be readily applied in EDs for minor procedures and longer acting forms of analgesia. Nerve blocks more applicable in the operating theatre or best done under ultrasound guidance are mentioned but not discussed in this article. This continuous professional development (CPD) article aims to provide guidance with respect to several key areas related to more commonly used types of regional anaesthesia in district level services. We discuss the importance of good clinical practice including thorough preparation of equipment and the patient to avoid common complications, clinical indications for regional blocks in the ED, local anaesthetic agents, different techniques for some common regional blocks, potential complications, and the need for a trained interprofessional team.